Symposium on Trout Habitat, Research, and Management Proceedings - Consortium Press, Appalachian (Appalachian State University, 1975)
Published in 1974, these symposia proceedings examine the management of trout habitat in mountain streams. Conservation organizations, researchers, and land managers, discussed trout habitat management programs and policies. They also identified management problems and present and explored future needs.